SANKSI PELAKU PIDANA EKSPLOITASI PEKERJA ANAK DI BAWAH UMUR DALAM PEKERJAAN YANG MEMBAHAYAKAN KESELAMATAN DAN MORAL PUTUSAN NO.88/PID.SUS.2019/PN.PTSB: Juridical Analysis of The Sanctions for The Perpetrators of Criminal Act of Exploitation of Child Labor in Endangering Safety and Morals - Syaida Radella Clarissa Chairy; Rini Purwaningsih (Faculty of Law, Universitas Trisakti, 2025)
Child exploitation in the world of work is a serious violation of children's rights, especially when it involves sexual aspects and work that can endanger safety and morals. The purpose of this research is to analyze the application of criminal penalties against perpetrators of child exploitation based on Decision Number 88/Pid.Sus/2019/PN.PTSB, as well as assess how effective the law is. The method used in this research is normative law. The research findings indicate that the defendant was sentenced to one year imprisonment and a fine of 200 million, in accordance with Article 185 jo Article 68 of Law No. 13 of 2003 concerning Manpower. However, these sanctions are considered lenient when compared to the penalty under Article 2 paragraph (1) of Law No. 21 of 2007on the Eradication of the Crime of Trafficking in Persons, which has a maximum of 15 years imprisonment and a fine of up to 600 million. This study research result and concludes that the application of criminal measures in this case has not been sufficient to provide a deterrent effect for violators or protection for exploited children. Law enforcement among perpetrators of child exploitation should take stricter measures, including strengthening the enforcement of more responsible articles with more severe threats to ensure better protection for children.